Efficacy of Group O Washed Red Blood Cell Transfusion on Vital Signs and Hematologic Stability in Trauma Patients With Different Blood Types - Gou XJ; Li LF; He XL; Chen X; Yu AY; Tian WY (Journal of Multidisciplinary Healthcare)
Xian-Juan Gou,1 Lin-Fei Li,1 Xiao-Li He,1 Xi Chen,2 An-Yong Yu,1 Wei-Yan Tian1 1Department of Emergency, Affiliated Hospital of Zunyi Medical University, Zunyi City, Guizhou Province, 563000, People’s Republic of China; 2School of Nursing, Zunyi Medical University, Zunyi City, Guizhou Province, 563000, People’s Republic of ChinaCorrespondence: Wei-Yan Tian, Department of Emergency, Affiliated Hospital of Zunyi Medical University, Zunyi City, Guizhou Province, 563000, People’s Republic of China, Tel +86 19184321912, Email 907359734@qq.comObjective: To comprehensively assess the impact of emergency transfusion of group O washed red blood cells on the vital signs and hematological parameters of patients with severe trauma and to analyze the differential responses among different blood types, thereby providing valuable evidence for optimizing transfusion strategies.Methods: A retrospective analysis was conducted on the clinical data of patients with severe trauma who underwent emergency transfusion in the hospital’s emergency department from April 2023 to March 2024. Changes in blood biochemical indexes and vital signs before and after transfusion were compared, and adverse transfusion reactions were monitored.Results: A total of 65 patients were included in the study, and no adverse transfusion reactions were observed. The shock index (SI) score was 1.07 ± 0.28. Significant changes were noted in platelet count (PLT), activated partial thromboplastin time (APTT), and C-reactive protein (CRP) following transfusion (P < 0.05). Both blood pressure and SI enhanced significantly after transfusion (P < 0.05), although no significant change in heart rate (HR) was detected (P = 0.87). Patients with blood group A experienced a significant reduction in HR post-transfusion. In patients with blood groups AB or O, systolic blood pressure (SBP) significantly increased, and SI significantly decreased. Additionally, patients with blood group O revealed a significant rise in diastolic blood pressure (DBP) post-transfusion, with the differences being statistically significant (P < 0.05).Conclusion: Timely and effective transfusion of group O washed red blood cells is crucial for stabilizing the vital signs of patients with severe trauma. This approach is not only safe but also feasible, with blood type influencing the response to transfusion. Larger, multi-center studies are warranted to further validate these findings and enhance the generalizability.Keywords: blood group, group O washed red blood cells, safety, severe trauma, shock index